Design of the Remote Wireless Meter Reading System Based on GPRS - Na Wu; Yinjing Guo; Yongqin Wei; Aying Wei (Institute of Advanced Engineering and Science, 2013)
Smart grid is the focus development direction of the national power grid construction, and remote power information collection is the important part of smart grid. The existing automatic meter reading system of remote electric power information collection has such problems as high cost, big power consumption, small networking and big line interference etc. Aim at these features, this paper proposes a new scheme of wireless meter reading based on GPRS, that is, the wireless communication module MC55 of SIMENS and STC89C58RD single chip are adopted as the core to develop a set of remote wireless meter reading system. The paper mainly introduces the overall design of the system, the hardware circuit and software design of each component, and the major software flow chart is given. The system has the characteristic of low cost, low power consumption, ad-Hoc network, self adaption, etc, and it has the strong portability and compatibility. Field test results show that the wireless meter reading system can finish the data collection and transmission task quickly and accurately, and has strong anti-interference ability and wide applicability. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2946